Research methodology for strategy as practice - Langley, Ann (Henry Stewart Talks, 2014)
The domain of “strategy as practice” research, Approaching strategy as practice (Epistemological choices and research strategies), Bounding strategy as practice (Sampling and research design), Capturing strategy as practice (Access, data collection and ethics), Understanding strategy as practice (Analysis and theorizing)